Blockage of Extracellular Signal-Regulated Kinase Exerts an Antitumor Effect via Regulating Energy Metabolism and Enhances the Efficacy of Autophagy Inhibitors by Regulating Transcription Factor EB Nuclear Translocation in Osteosarcoma - Zhang, Man; Bai, Yang; Xu, Chang; Qi, Yiying; Meng, Jiahong; Zhang, Wenkan; Su, Hang; Yan, Weiqi (Frontiers in Cell and Developmental Biology, 2021)
Accumulating evidence suggests that extracellular signal-regulated kinase (ERK) is a valuable target molecule for cancer. However, anti-tumor drugs targeting ERK are still in their clinical phase and no FDA-approved medications exist. In this study, we identified an ERK inhibitor (ERKi; Vx-11e) with potential antitumor activities, which was reflected by the inhibition in the survival and proliferation of osteosarcoma (OS) cells. Mechanistically, the ERKi regulated autophagic flux by promoting the translocation of transcription factor EB (TFEB) in OS cells, thereby increasing the dependence of OS cells on autophagy and sensitivity to treatment with autophagy inhibitors in OS. Besides, we also found that the ERKi could regulate mitochondrial apoptosis through the ROS/Mitochondria pathway and aerobic glycolysis in OS, which also increases the dependence of OS cells on autophagy to clear metabolites to a certain extent. These results may provide a reference for the clinically improved efficacy of ERKis in combination with autophagy inhibitors in the treatment of OS and indicate its potential as a therapeutic agent.